Medicinal Plants : Conservation and Sustainable Use in Sri Lanka - World Bank (World Bank, Washington, DC, 2012)
In Sri Lanka, ayurveda (a holistic system of medicine and health care which originated in India-in Sanskrit, "Ayu" means " life' and "veda" means " the knowledge of ") and the traditional system of health care have been systematically used for over two thousand years to treat illnesses. When last listed, 1,414 plant species have been used for this purpose. These species include several endemic species which are becoming increasingly rare and under threat of extinction. Approximately 200 species of medicinal plants are in common use, and of these 50 are heavily used in ayurvedic and traditional health care systems. Nearly 80 medicinal plant species are now considered threatened. In addition to recognizing their curative and therapeutic value, Sri Lankans uses medicinal plants in rituals, cultural activities and in religious functions.